Idioms and Ambiguity in Context : Phrasal and Compositional Readings of Idiomatic Expressions - Wiltrud Wagner (De Gruyter, 2020)
Idioms have long been of interest to research in linguistics as well as literary studies. In the existing research, however, the aesthetic productivity of idiomatic ambiguity has never been in focus. The present study on Idioms and Ambiguity in Context fills this gap by analyzing a corpus of children's literature—traditionally characterized by a high measure of wordplay and ambiguity—both in a linguistic and literary perspective. Looking at the connection between context and understanding of idiomatic expressions in either their phrasal or their compositional reading, the study explores how ambiguity is activated, if, how, and when it is perceived on the different levels of communication, and how literary texts use this ambiguity in playful ways.